2004
DOI: 10.1111/j.1360-0443.2004.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal cocaine use does not appear to be an independent risk factor for HCV infection

Abstract: While there was a high prevalence of anti-HCV antibodies in this sample of intranasal cocaine users, the infection was highly correlated with the presence of intravenous (i.v.) drug use and duration of drug use. In this sample, therefore, intranasal cocaine use alone was not an important risk factor for HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Risk levels appear to vary substantially by location [5,6,24-26]. HCV prevalence in non-injecting drug users range from 2% to 38% in different parts of the world [3,8,11,27-29]. Epidemiological studies of illicit-drug users in the Northeast, Midwest, South and Southeast regions of Brazil (including both injecting and non-injecting drug users) have recorded prevalence of HCV infection between 5% and 36% [9-14].…”
Section: Discussionmentioning
confidence: 99%
“…Risk levels appear to vary substantially by location [5,6,24-26]. HCV prevalence in non-injecting drug users range from 2% to 38% in different parts of the world [3,8,11,27-29]. Epidemiological studies of illicit-drug users in the Northeast, Midwest, South and Southeast regions of Brazil (including both injecting and non-injecting drug users) have recorded prevalence of HCV infection between 5% and 36% [9-14].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, 21 as well as in groups of intranasal cocaine users 53 and alcohol abusers, 54 injection drug use has been shown to be an established risk factor for HCV infection. In our study, this association was clearly demonstrated in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…We found 28 published reports that met our criteria (Allwright et al, 2000;Baozhang et al, 1997;Broers et al, 1998;Chang et al, 1999;Denis et al, 2000;Feldman et al, 2000;Fuller et al, 2004;Galperim et al, 2004;Garten et al, 2004;Gyarmathy et al, 2002;Harsch et al, 2000;Hershow et al, 1998;Howe et al, 2005;Koblin et al, 2003;Lai et al, 2001;Maayan et al, 1994;Mathei et al, 2005;Njoh et al, 1997;Nyamathi et al, 2002;Quaglio et al 2003a;Quaglio et al 2003b;Santana Rodriguez et al, 1998;Shrestha et al, 1998;Strasfeld et al, 2003;Tortu et al, 2001;Tortu et al, 2004;Van Ameijden et al, 1993;Ward et al, 2000). One report included two separate studies, both of which were included (Tortu et al, 2001) and which appear in Table 1 in two separate rows; two reports were by the same author and indicated the same overall seroprevalence and sample size, therefore we counted this as one study (Quaglio et al 2003a(Quaglio et al & 2003b.…”
Section: Study Characteristicsmentioning
confidence: 91%